Bees and palms in Peninsular Malaysia - Kiew, Ruth; Muid, Mohamad (International Palm Society, 1989)
Bees which in Malaysia have been observed visiting palms belong to the genera Apis and Trigona. These include the two important honeybees in Malaysia, the Malaysian honeybee, Apis cerana indica, which can be kept in hives, and the giant honeybee, Apis dorsata. The sweat bees, Trigona spp., are important pollinators in the rain forest but they accumulate very little honey.